2010
DOI: 10.1093/sleep/33.3.343
|View full text |Cite
|
Sign up to set email alerts
|

Association between a Serotonin Transporter Length Polymorphism and Primary Insomnia

Abstract: This finding contributes to the understanding of the pathophysiology of primary insomnia and suggests a biological basis between the prevalent comorbidity of primary insomnia and other psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 29 publications
4
61
0
5
Order By: Relevance
“…An implication of our finding is that identification of genes for one of the three symptoms can help search genes for the other symptoms. Recent molecular genetic studies have shown that the serotonin system genes are involved in susceptibilities to all three symptoms (Deuschle et al, 2010;Falkenberg et al, 2011;Uher & McGuffin, 2008), which support our results. In our best-fitting model, symptom-specific genetic variances were relatively small.…”
Section: Discussionsupporting
confidence: 91%
“…An implication of our finding is that identification of genes for one of the three symptoms can help search genes for the other symptoms. Recent molecular genetic studies have shown that the serotonin system genes are involved in susceptibilities to all three symptoms (Deuschle et al, 2010;Falkenberg et al, 2011;Uher & McGuffin, 2008), which support our results. In our best-fitting model, symptom-specific genetic variances were relatively small.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, two studies to date have found that the 'short' allele conferred greater risk for sleep disturbances, including problems such as insomnia. (91,92) However, a recent candidate gene study focusing on 5HTTLPR by our group found that 'long-long' homozygotes experienced poorer sleep quality than carriers of at least one 'short' allele. (93) It is possible that these discrepant findings are due to differences in sample composition.…”
Section: Specifying Genes and Environmentsmentioning
confidence: 94%
“…32 , 34 , 35 Candidate gene studies have identifi ed gene variants that may be involved in the pathophysiology of insomnia, including Apo ε 4, 36 PER3 4/4 , 37 HLA DQB1 * 0602, 38 homozygous Clock gene 3111C/C Clock, 39 and short (s-) allele of the 5-HTTLPR. 40 A genomewide association study found numerous single-nucleotide polymorphisms (SNPs) signifi cantly associated with insomnia symptoms. 41 Th e most signifi cant SNPs occurred within genes involved in neuroplasticity (eg, ROR1, PLCB1, EPHA4, and CACNA1A), stress reactivity (eg, STK39, USP25, and MARP10), neuronal excitability (eg, GABRB1 and DLG2), and mental health (eg, NPAS3).…”
Section: Genetics Of Sleep and Insomniamentioning
confidence: 99%